THE PERCEPTION OF PHYSIOTHERAPISTS OF KARACHI IN THEIR ROLE TO REHABILITATE AND MANAGE OBESITY (International Journal of Physiotherapy, 2016)
Background: Physiotherapists as providers of primary health care are well placed in promoting physical activity and lifestyles changes, but the role and practice of physiotherapist towards its promotion among obese individuals has not been fully investigated. The objective of this study is to examine perceptions of Karachi physiotherapists regarding their role in management of obesity, the learning needs for, and hurdles facing by them in the rehabilitation.Methods: It was cross-sectional survey that has been conducted among 100 Physiotherapists from three tertiary care hospitals & universities of Karachi from April to June 2013. There has been used Self-administered questionnaire and sampling was Convenient Purposive sampling in qualitative research. Descriptive statistics were calculated for all variables using the Statistical Package for the Social Sciences (SPSS) version 17. Questionnaire was intended to determine physiotherapist’s perceptions of their role and consisted of questions about respondent’s demographics profile, practice and domains related to management of obesity and associated conditions.Result: In this study 93% of participants agreed that physiotherapists has role in the management of patients with obesity by developing exercise interventions.95% plays role in functional mobility and 94%in cardio respiratory training programme. In this study participants were found less aware about weight loss management. Barrier found in patient treatment is due to lack of patient motivation.Conclusion: This study revealed physiotherapist played important role in patient rehabilitation management with obesity, especially in a area of mobility and exercise prescription for conditions associated with obesity. In future there is need to take into account the different perspectives of physical therapy and with a larger sample size representing all four states of Pakistan.